2003
DOI: 10.1063/1.1618367
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive transverse load sensing with reversible sampled fiber Bragg gratings

Abstract: We present the implementation of optical load sensors utilizing mechanically induced reversible sampled fiber Bragg gratings (SFBGs). The load is measured by the reflectivity of the first-order Fourier component of the induced SFBGs. The theoretical and experimental characterization indicates that such SFBGs can be tailored to realize load sensors with high sensitivity of near-linear response and free of influence from environmental and system noises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…Thus various grating-based pressure sensors have been developed to measure the applied transverse load. 87,[143][144][145][146][147][148] Pressure sensors based on conversional UV-laser-induced gratings usually, however, fail to determine the direction of the applied force due to their symmetric transverse-loading characteristics. The CO 2 -laser-induced LPFGs exhibit asymmetric transverse-loading characteristics due to the load-induced birefringence that leads to the rotation of optical principal axes in the gratings.…”
Section: E Pressure Sensorsmentioning
confidence: 99%
“…Thus various grating-based pressure sensors have been developed to measure the applied transverse load. 87,[143][144][145][146][147][148] Pressure sensors based on conversional UV-laser-induced gratings usually, however, fail to determine the direction of the applied force due to their symmetric transverse-loading characteristics. The CO 2 -laser-induced LPFGs exhibit asymmetric transverse-loading characteristics due to the load-induced birefringence that leads to the rotation of optical principal axes in the gratings.…”
Section: E Pressure Sensorsmentioning
confidence: 99%
“…[1][2][3][4][5] Thus far, the FBG sensors' capability to measure physical quantities such as the temperature, strain, pressure, etc., has been studied extensively. [2][3][4][5][6][7][8] However, the use of FBG sensors for detection of environmental refractive index change has not been fully explored. Refractive index sensing is important for biological and chemical applications since a number of substances can be detected through measurements of the refractive index.…”
mentioning
confidence: 99%
“…Fiberoptic sensors based on fiber Bragg gratings [22][23][24][25][26] or long period gratings [27] have been reported for transverse load sensing. In this paper, we demonstrated that the transverse load sensing can be realized by using the proposed bubble-structure micro-cavity.…”
Section: Characterization Of Fiber Tip Micro-cavity Sensorsmentioning
confidence: 99%